The autophagy machinery restrains iNKT cell activation through CD1D1 internalization. Issue 6 (3rd June 2017) - Keller, Christian W.; Loi, Monica; Ewert, Svenja; Quast, Isaak; Theiler, Romina; Gannagé, Monique; Münz, Christian; De Libero, Gennaro; Freigang, Stefan; Lünemann, Jan D.
ABSTRACT: Invariant natural killer T (iNKT) cells are innate T cells with powerful immune regulatory functions that recognize glycolipid antigens presented by the CD1D protein. While iNKT cell-activating glycolipids are currently being explored for their efficacy to improve immunotherapy against infectious diseases and cancer, little is known about the mechanisms that control CD1D antigen presentation and iNKT cell activation in vivo. CD1D molecules survey endocytic pathways to bind lipid antigens in MHC class II-containing compartments (MIICs) before recycling to the plasma membrane. Autophagosomes intersect with MIICs and autophagy-related proteins are known to support antigen loading for increased CD4 + T cell immunity. Here, we report that mice with dendritic cell (DC)-specific deletion of the essential autophagy gene Atg5 showed better CD1D1-restricted glycolipid presentation in vivo. These effects led to enhanced iNKT cell cytokine production upon antigen recognition and lower bacterial loads during Sphingomonas paucimobilis infection. Enhanced iNKT cell activation was independent of receptor-mediated glycolipid uptake or costimulatory signals. Instead, loss of Atg5 in DCs impaired clathrin-dependent internalization of CD1D1 molecules via the adaptor protein complex 2 (AP2) and, thus, increased surface expression of stimulatory CD1D1-glycolipid complexes. These findings indicate that the autophagic machinery assists in the recruitment of AP2 to CD1D1 molecules resulting in attenuated iNKT cell activation, in contrast to the supporting role of macroautophagy in CD4 + T cell stimulation.